Isolasi dan Karakterisasi Senyawa Metabolit Sekunder Fraksi Etil Asetat Daun Sungkai (Peronema canascane Jack.) - Suryati; Aulia Liberty; Norman Ferdinal; Emil Salim (Departemen Kimia Universitas Andalas, 2026)
Peronema canescens Jack, locally known as Sungkai, is a medicinal plant widely found in Indonesia and traditionally used as an antipyretic, anthelmintic, antimalarial, and mouthwash. Due to its diverse pharmacological potential, Sungkai leaves represent a promising subject for research. This study aimed to isolate and characterize secondary metabolites from the ethyl acetate fraction of Sungkai leaves collected from Agam Regency. The isolation process was carried out using column chromatography followed by purification through trituration, yielding 4.2 mg of white solid. Purity analysis by thin- layer chromatography (TLC) showed a single purple spot after spraying with Liebermann–Burchard reagent, with a melting point in the range of 251–253 °C. UV–Vis spectrophotometry exhibited a maximum absorption at 284 nm, indicating the presence of a limited conjugated system. FTIR spectrum confirmed the presence of aliphatic C–H stretching (2919 cm⁻¹), C=C stretching (1635.41 cm⁻¹), geminal dimethyl group (1450.30 cm⁻¹), and C–O stretching (1028.88 cm⁻¹). Based on these results, the isolated compound was identified as a member of the triterpenoid class.